2013
DOI: 10.3724/sp.j.1006.2013.01644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress During Grain Filling on Sugar Accumulation and Enzyme Activity Associated with Sucrose Metabolism in Sweet Corn

Abstract: With the trends of global warming, the extreme high temperature stress often happens during crop grain filling in the world. Heat stress has been an important factor limiting grain yield and quality. To determine the effects of heat stress on fresh kernel yield, quality and enzyme activities of sucrose metabolism, we carried out an experiment in artificial phytotron using two sweet corn cultivars (Xiatian 1 and Yuetian 16) with two typical temperature treatments (high temperature, HT and control, CK) during gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
(17 reference statements)
1
20
0
Order By: Relevance
“…Later on, this difference no longer existed. A study on sweet maize showed that the activities of SuSy were decreased throughout grain filling 8 . The reduced activities of SPS and SuSy restrained sucrose synthesis 26 , 30 and increased grain starch content before 15 DAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, this difference no longer existed. A study on sweet maize showed that the activities of SuSy were decreased throughout grain filling 8 . The reduced activities of SPS and SuSy restrained sucrose synthesis 26 , 30 and increased grain starch content before 15 DAP.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures for enzyme extraction were carried out in ice (0 °C–2 °C). The embryo and pericarp of the grains were removed, and approximately 1 g fresh weight of the lyophilized samples were homogenized in the extraction buffer containing 50 mM HEPES-NaOH (pH 7.5) followed by centrifugation at 10,000 × g for 10 min 8 . The supernatant was used for enzyme assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reverse reaction, sucrose can be synthesized from glucose and fructose by SS-synthesis or SPS in the presence of UDP-glucose (UDPG). Sucrose also modulates the response in field and model plants to cold , heat (Zhao et al, 2013), drought (Hoffmann, 2010), and anoxia (Lara et al, 2011). Sucrose may protect the cytomembrane by acting as a cytoprotectant, scavenge reactive oxygen species (ROS), act as a signaling molecule, and regulate gene expression to protect plants against stress .…”
mentioning
confidence: 99%
“…Extraction of SuSy (EC 2.4.1.13) and determination of its activity were performed as described by Zhao et al () and Zhang et al () with modifications. A reaction medium composed of 50 mM MOPS‐NaOH (pH 7.5), 10 mM MgSO 2 , 10 mM fructose, 10 mM fructose, and 5 mM uridine 5′‐diphosphate glucose was used.…”
Section: Methodsmentioning
confidence: 99%